Groundswell Africa : A Deep Dive into Internal Climate Migration in Nigeria - Rigaud, Kanta Kumari; de Sherbinin, Alex; Jones, Bryan; Abu-Ata, Nathalie E.; Adamo, Susana (World Bank, Washington, DC, 2021)
The World Bank’s flagship report, Groundswell: Preparing for Internal Climate Migration (Rigaud et al. 2018), and the sequel (Clement et al. 2021), finds that that Sub-Saharan Africa is likely to witness high levels of climate-induced mobility. An expanded and deeper analysis through Groundswell Africa, focusing on West African countries, reaffirms this pattern region (Rigaud et al. 2021a). The recent study projects that by 2050, without concrete climate and development action, West Africa could see as many as 27.3 million people move because of slow-onset climate impacts, such as water stress, drops in crop and ecosystem productivity, and sea level rise compounded by storm surge. These spatial population shifts will represent 3.48 percent of the total population of West Africa. Understanding the scale and the patterns of these climate-induced spatial population shifts is critical to inform policy dialogue, planning, and action to avert, minimize, and better manage climate-induced migration for dignified, productive, and sustainable outcomes. Nigeria has a long history of mobility, and migration patterns have historically been dynamic. The migration towards north-central zones as well as southward toward Lagos and other coastal cities is influenced by climate change and environmental conditions as well as better economic opportunities. In recent years, severe floods have led to loss of lives, housing and infrastructure, and compelled Nigerians to move out of areas affected by the disasters.